Proactive corporate environmental strategy and the development of competitively valuable organizational capabilities - Sharma, Sanjay; Vredenburg, Harrie (Strategic Management Journal, 1998)
This article presents the results of a study conducted in two phases within a single industry context. The first phase involved comparative case studies to ground the applicability of the resource-based view of the firm within the domain of environmental responsiveness. The second phase involved testing the relationships observed during the case studies through a mail survey. It was found that strategies of proactive responsiveness to the uncertainties inherent at the interface between the business and ecological issues were associated with the emergence of unique organizational capabilities. These capabilities, in turn, were seen to have implications for firm competitiveness. © 1998 John Wiley & Sons, Ltd.